ANALYSIS TECNICAL AND TROLL LINE FISHING FISHERIES BUSINESS AT BUNGUS OCEANIC FISHING PORT (PPS BUNGUS) WEST SUMATERA PROVINCE - Wiladri, Putri; Brown, Arthur; Bustari, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The purposes of research were to analyzed technical aspect of troll line fishing gear and to assessed economical aspects of asset, cost, revenue, and profit. To count the BCR (Benefit Cost Ratio), PP (Payback Period) and FRR (Financial Rate of Return) for financial fishing analysis. The research was conducted in July 2018 in Bungus Oceanic Fishing Port (PPS Bungus) West Sumatera Province. The method used in this research is survey method. Primary data collection directly by involved the fishing operation and interviews with the questionnaire to get information data the financial analysis. The secondary data was collected in research-supported instantions. The result of the research shown, troll line fishing gear use hook no. 4 for fishing. The main line between 80 m. Troll line fishing gear use the ship with 12,85 m long and 1,7 m width. The ship use Yanmar 33 machine with power 26 HP to operate in the sea. The average revenue of fisherman was Rp 804.000.000,- with total cost Rp 629.612.000,- per year and profit Rp 174.388.000 per year. The result of a financial analysis were BCR 1,27,- , PP 1,2 tahun and 85% for FRR. From these result, fisheries business with troll line fishing gear in Bungus Oceanic Fishing Port West Sumatera province  is profitable and feasible to do Keywords : Technical Analysis; Financial Analysis; Troll line Fishing Gear; Bungus Oceanic Fishing Port